Aspergillus niger as a cell factory for the production of pyomelanin, a molecule with UV-C radiation shielding activity - Koch, Stella Marie; Freidank-Pohl, Carsten; Siontas, Oliver; Cortesao, Marta; Mota, Afonso; Runzheimer, Katharina; Jung, Sascha; Rebrosova, Katarina; Siler, Martin; Moeller, Ralf; Meyer, Vera (Frontiers in Microbiology, 2023)
Melanins are complex pigments with various biological functions and potential applications in space exploration and biomedicine due to their radioprotective properties. Aspergillus niger, a fungus known for its high radiation resistance, is widely used in biotechnology and a candidate for melanin production. In this study, we investigated the production of fungal pyomelanin (PyoFun) in A. niger by inducing overproduction of the pigment using L-tyrosine in a recombinant ΔhmgA mutant strain (OS4.3). The PyoFun pigment was characterized using three spectroscopic methods, and its antioxidant properties were assessed using a DPPH-assay. Additionally, we evaluated the protective effect of PyoFun against non-ionizing radiation (monochromatic UV-C) and compared its efficacy to a synthetically produced control pyomelanin (PyoSyn). The results confirmed successful production of PyoFun in A. niger through inducible overproduction. Characterization using spectroscopic methods confirmed the presence of PyoFun, and the DPPH-assay demonstrated its strong antioxidant properties. Moreover, PyoFun exhibited a highly protective effect against radiation-induced stress, surpassing the protection provided by PyoSyn. The findings of this study suggest that PyoFun has significant potential as a biological shield against harmful radiation. Notably, PyoFun is synthesized extracellularly, differing it from other fungal melanins (such as L-DOPA- or DHN-melanin) that require cell lysis for pigment purification. This characteristic makes PyoFun a valuable resource for biotechnology, biomedicine, and the space industry. However, further research is needed to evaluate its protective effect in a dried form and against ionizing radiation.